Comparative Analysis of Basic and Extended Power Models of Boreholes Expansion Dependence on Explosive Charge in Blasting in Clay Soil - Ivan Kovač; Denis Težak; Josip Mesec; Ivica Markovinović (Geosciences, 2020)
Spherical cavities made by explosive charge activation in a clay soils differ in size and shape. The mass of explosive charge lowered on the bottom of the borehole in a one-time blasting is typically relatively small and is calculated by a desired and planned performace. The effect of smaller explosive charge for spherical cavities is in principle different than continuously filled borehole in mining and blasting operations. Detonation of smaller explosive charge crushes the material in proximity of activated explosive charge. With the increase of distance from the explosive charge, the released energy in not enough for crushing of the materials, but instead compacts it. This paper is an extension of the previous research, which resulted in a smallest error of estimated in a model shown as the sum of square residuals (SS), largest value of determination coefficient (R2) and smallest loss of information through Akaike’s Information Criteria (AIC and AICc). This paper presents an extended power model of dependence of spherical cavity volume expansion on explosive charge. Extended model is a basic model with an additional parameter to ensure more precise mathematical description and further decrease of error of estimate for all efficiency indicators and for both types of explosive used.